An assessment of selected restrooms based on the Philippine accessibility law - Acosta, Reverie B. (College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT The purpose of the study was to determine whether selected restrooms in food and beverage establishments complied with the Philippine Accessibility Law or BP 344. The research was a quantitative study which employed observation and photographic documentation. Nine restrooms were chosen for the study using stratified random sampling. The instrumentation used for data gathering was a checklist, a notebook, and a camera. Based on the results of the study, the Philippine Accessibility Law or BP 344 had not been properly implemented in the selected restrooms. None of the nine restrooms were fully compliant with the provisions found in BP 344. The highest score in terms of compliance was 14/17 or 82 percent. The aspect of the law that was most complied with was the prescribed water closet dimension while the least complied with was the prescribed lavatory dimension. The noncompliance may be attributed to the proximity of a number of public restrooms in these shopping malls to the selected food and beverage establishments, all of which had restrooms especially designed for people with disabilities. The noncompliance may also be attributed to the architect or designer's knowledge of the law which corresponds to the manner of installation of restroom fixtures and accessories.